Serum Magnesium Level in Gestational Diabetes Mellitus in a Tertiary Care Hospital of Bangladesh (Bangladesh Journal of Medical Biochemistry, 2018)
Gestational diabetes mellitus (GDM) is characterized by glucose intolerance during pregnancy. GDM is associated with an increased incidence of congenital abnormalities usually aggravated by maternal magnesium deficiency. Magnesium is one of the essential trace elements for normal embryogenesis and foetal growth and its deficiency increases mortality and morbidity rate of mothers, embryos and neonates. The present study was undertaken to evaluate the association of serum magnesium with GDM in second and third trimester of pregnancy. This case-control study was conducted in Mymensingh Medical College Hospital during the period from July 2013 to June 2014 to evaluate the association of serum magnesium with GDM in Bangladeshi women. A total of 172 subjects were recruited in this study; among them eighty six women with GDM were selected as case (Group-I) and eighty six healthy pregnant women were taken as control (Group- II). The cases again were subdivided as Group Ia and Ib at second and third trimester respectively. Controls also were subdivided as Group IIa and IIb at second and third trimester respectively. Student's unpaired 't' test was used to compare the data between groups. For analytical purpose 95% confidence limit (p